2021
DOI: 10.1186/s12934-021-01568-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome analysis reveals gut microbiota alteration of early-weaned Yimeng black goats with the effect of milk replacer and age

Abstract: Background Colonization of intestinal microbiota in ruminant during the early life is important to host health, metabolism and immunity. Accumulating evidence revealed the ameliorative effect of milk replacer administration in the gut microbial development of early-weaned ruminants. Yimeng black goats (YBGs) inhabiting Shandong, China show a complex intestinal microbial ecosystem, but studies of their gut microbiota are still insufficient to report. Here, this study was performed to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 60 publications
5
30
0
Order By: Relevance
“…Anecdotal evidence indicated that the gut microbiota vary dynamically within limits and affected by species, age and feed, but these physiological fluctuations cannot impair the normal intestinal functions [ 31 , 32 ]. However, the ecological balance of of gut microbiota can be disrupted by multiple factors including diabetes, antibiotics and diarrhea [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotal evidence indicated that the gut microbiota vary dynamically within limits and affected by species, age and feed, but these physiological fluctuations cannot impair the normal intestinal functions [ 31 , 32 ]. However, the ecological balance of of gut microbiota can be disrupted by multiple factors including diabetes, antibiotics and diarrhea [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study indicated that Firmicutes , Bacteroidetes , Ascomycota and Basidiomycota were the most preponderant microbial phyla in yaks, regardless of health status, which was in line with previous investigations on yaks [ 24 ]. Additionally, these dominant phyla were also demonstrated to be extensively existed in the goats, giraffes and cattle, indicating their importance in intestinal ecology and functions in ruminants [ 31 , 41 ]. Some specific bacterial and fungal alternations may reflect the potential relationship between diarrhea and gut microbiota, thus we further characterized the intestinal bacteria and fungi associated with diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that compared with prepartum mares, postpartum mares had an increased relative abundance of the Firmicutes phylum (specifically family Streptocococcaceae) and a corresponding decrease in the relative abundance of the family Lachnospiraceae (also in the Firmicutes phylum) ( Weese et al, 2015 ). Generally, Clostridium sensu stricto and Streptococcus commonly considered two opportunistic pathogens of the animal intestine ( Milinovich et al, 2008 ; Boyle et al, 2018 ; Liang et al, 2018 ; Li et al, 2021 ). For instance, enrichment of Streptococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Lachnospiraceae and Ruminococcaceae were mainly enriched in MP. Genera from the families Lachnospiraceae and Ruminococcaceae exhibit anti-inflammatory functions including Ruminococcaceae_UCG-005 , and are also reported to be involved in the production of short-chain fatty acids (SCFAs) ( Liu et al, 2019 ; Vojinovic et al, 2019 ; Li et al, 2021 ; Liao R. et al, 2021 ), which are essential for the regulation of intestinal microbiota balance and the maintenance of intestinal epithelium integrity ( Tan et al, 2014 ; Kelly et al, 2015 ). Moreover, Ruminococcaceae bacteria have the ability to degrade cellulose and starch, which is closely related to feed efficiency in herbivorous animals ( Zhao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…By systematically exploring and comparing acquired information, the relationship between gut microbiota and diseases could be further understood, and prevention and control measures can be developed to minimize economic losses ( 21 23 ). Presently, the complicated composition and structure of gut microbiota in diarrheic pigs, yaks, and giraffes have been successfully analyzed based on the high-throughput sequencing technology ( 24 26 ). However, there are few reports on the gut microbiota of horses, and even fewer studies on the composition and structure of gut microbiota in horses in different health statuses.…”
Section: Introductionmentioning
confidence: 99%